(untitled) (Altre Modernità, 2020)
“It is this effort of voluntary absence, of voluntary uprooting, of active distancing compared to its environment which always appears natural, it is then the way to get away from oneself -even if for one moment or only temporarily-, to separate from the roots, the national and all of what is, more generally, fixed in a narrow identity, it is this and above all what I would call wandering” (Mizubayashi 107-108). This extract from Petit éloge de l’errance from Akira Mizubayashi, a Japanese writer of French expression, places us at the center of the interior nomadism theme, evoking his deliberate choice for wandering, of the Japanese society. Wandering which is understood as a decline in identity and questioning, but also as discovery of Western culture. In his writings, the author shows his affection, his attachment to the language, literature, and French culture but he also points out the complex multicultural and pluralist relationship which lies between nation, language and identity. Our purpose is to highlight how an author as Akira Mizubayashi, who refused the conformism and condemns the Japanese society, appropriates a new reality, endorsing a language and a culture that does not convey the representations to which he had escaped breaking, so as he points out, “the locks of asphyxiating identities” (Mizubayashi 89).